The structure of the Forex Bureau Market of Ghana (Journal of Science and Technology, 2016)
The forex bureau market has been in operation for a while now. But does the public know how much activity is going on in this market? Who buys and sells to this mini financial market? How much do people buy and sell at a time? Which currencies are more easily exchanged on this market? This article tries to answer the above questions as well as others concerning this relatively new market.